A ‘EXTRAVAGÂNCIA’ DE TRABALHAR DOENTE: O CORPO NO TRABALHO EM INDIVÍDUOS COM DIAGNÓSTICO DE LER/DORT - Dale, Alana Pires; Dias, Maria Dionísia Do Amaral (Fundação Oswaldo Cruz, Escola Politécnica de Saúde Joaquim Venâncio, 2018)
Abstract Among the most prevalent occupational diseases are the Repetitive Strain Injury and Work-Related Musculoskeletal Disorders (RSI/WRMD), which are directly related to the organization of the work that ignores the limits of the body and the uniqueness of each worker. The study main focus was to investigate the significance of the body at work in individuals diagnosed with lesion/disturb. To achieve the proposed objective, a case study was held in a qualitative approach, which is based in the socio-historical theory of psychology. The means used to achieve the data was through individual open interviews with nine subjects whom had been diagnosed with RSI/WRMD and were accompanied at the Worker's Health Reference Center in Botucatu (São Paulo, Brazil). As a result, three meaning cores have been revealed: need to work - the ‘body’ in motion; body submission - lack of autonomy/power; and prevented body — ‘I caught, I stopped in my life’. In addition to these, meanings and explanatory material have composed the illustrator scheme of results of this research. The phrase that best defines the whole process of health/disease measured in the interviews according to the scenario reported by the individuals is ‘The extravagance of working sick’, and the product of this, is an uncertain future.

Resumen Entre las enfermedades profesionales con mayor prevalencia se encuentran las lesiones por esfuerzos repetitivos/enfermedades profesionales osteomusculares (LER-EPO), las cuales se relacionan directamente con la organización del trabajo que ignora los límites del cuerpo y las particularidades de los trabajadores. El objetivo principal del estudio que dio origen a este artículo fue investigar los significados del cuerpo en el trabajo, en individuos con este tipo de lesión/enfermedad. Para alcanzar el objetivo propuesto, se realizó un estudio de caso con enfoque cualitativo, fundamentado en la teoría socio-histórica de la psicología. Se utilizaron entrevistas abiertas individuales para la recolección de datos, realizadas con nueve participantes, los cuales tenían diagnóstico de lesiones por esfuerzos repetitivos/enfermedades profesionales osteomusculares y tenían seguimiento del Centro de Referencia en Salud del Trabajador de Botucatu (São Paulo, Brasil). El análisis de los datos reveló tres núcleos de significación: necesidad de trabajar —el cuerpo en movimiento; sumisión del cuerpo —falta de autonomía/poder; y cuerpo impedido —'tuve un bloqueo, mi vida se detuvo’. En base a estos núcleos, se identificaron los significados y los elementos explicativos; El presentismo se destacó entre los significados encontrados. La expresión que mejor define todo el proceso salud-enfermedad de los participantes es ‘la extravagancia de trabajar enfermo’, y el producto de éste es un futuro incierto.

Resumo Dentre as doenças do trabalho mais prevalentes estão as lesões por esforços repetitivos/distúrbios osteomusculares relacionados ao trabalho, as quais relacionam-se diretamente à organização do trabalho que ignora os limites do corpo e as singularidades dos trabalhadores. O objetivo deste artigo foi investigar os significados do corpo no trabalho em indivíduos com esse tipo de lesão/distúrbio. Para alcançar o objetivo proposto, fez-se um estudo de caso com abordagem qualitativa, a qual está embasada na teoria sócio-histórica da psicologia. Utilizaram-se entrevistas abertas individuais para coleta de dados, realizadas com nove participantes, os quais tinham diagnóstico de lesões por esforços repetitivos/distúrbios osteomusculares relacionados ao trabalho e eram acompanhados no Centro de Referência em Saúde do Trabalhador de Botucatu (São Paulo). A análise dos dados revelou três núcleos de significação: necessidade de trabalhar — o corpo em movimento; submissão do corpo — falta de autonomia/poder; e corpo impedido — ‘eu travei, eu parei minha vida’. Com base nesses núcleos foram identificados os significados e os elementos explicativos. O presenteísmo destacou-se entre os significados encontrados. A expressão que melhor define todo o processo saúde-doença dos participantes é ‘a extravagância de trabalhar doente’, e o produto deste é um futuro incerto.
THE ‘EXTRAVAGANCE’ OF WORKING SICK: THE BODY WORK IN INDIVIDUALS DIAGNOSED WITH RSI/WRMD
LA ‘EXTRAVAGANCIA’ DE TRABAJAR ENFERMO: EL CUERPO EN EL TRABAJO EN INDIVIDUOS CON DIAGNÓSTICO DE LER/EPO
Keywords: RSI-WRMD; significance of the body; occupational diseases; occupational health; work organization; LER-DORT; significados do corpo; doenças profissionais; saúde do trabalhador; organização do trabalho